Penerapan Model Pembelajaran Explicit Instruction Untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Kelas II SD Inpres Wailan - Mersty E. Rindengan (Peneliti.net, 2022)
The aims of this research are: to improve the results of Indonesian language learning regarding beginning reading material through the application of the Explicit Instruction Learning Model for Grade II SD Inpres Wailan. The actions taken in this research process used the class action research method (CAR) to collect and measure students' success in learning Indonesian language learning which was carried out in two cycles. This research method uses a research flow by following a systematically arranged flow as follows: 1) Planning (Plening), 2) Implementation of Action (Action), 3) Observation (Observation), and 4) Reflection (Reflection). The results of learning in the first cycle, the results of student learning completeness only reached a completeness value of 59%. Whereas in cycle II, through the action learning process, it was found that the results of student learning completeness increased to 86%. The conclusion is: Through the application of the Explicit Instruction learning model, in the Indonesian language learning process with the subject matter